Treasures from Korea arts and culture of the Joseon Dynasty, 1392-1910 - Woo, Hyunsoo; Kim, Hongkyung; Cho, Insoo; Song, Unsok; Lee, Rose; Kwon, So-hyun; Kim, Woollim; Moon, Dongsoo; Philadelphia Museum of Art.; Los Angeles County Museum of Art; Museum of Fine Arts, Houston (New Haven Yale University Press, 2014)
The Joseon dynasty left a substantial legacy for modern Korea, influencing contemporary etiquette, cultural norms, and societal attitudes. This book intends to survey the artistic production of the world's longest-ruling Confucian dynasty, which reigned on the Korean peninsula from 1392 to 1910
t Confucianism and the Art of the Joseon Dynasty / |r Insoo Cho -- |t Joseon: A Dynasty Founded on the Confucian Classics / |r Hongkyung Kim -- |t Screen Paintings of the Joseon Court / |r Hyunsoo Woo -- |t Ceramics and Ritual Vessels of the Royal Household / |r So-hyun Kwon -- |t The Collection and Appreciation of Scholarly Accoutrements and Sarangbang Culture in the Joseon Dynasty / |r Woollim Kim -- |t Buddhism and Art in the Joseon Royal House: Buddhist Sculpture and Painting / |r Unsok Song -- |t The Reception of a New Culture and Establishment of a New Visual System in Korea's Modern Era / |r Dongsoo Moon -- Catalogue. The King and His Court ; Joseon Society ; Ancestral Rituals and Confucian Values ; Continuity and Change in Joseon Buddhism ; Joseon in Modern Times.
Publicado en ocasión de la exposición celebrada en el Museo de Arte de Filadelfia, del 2 de marzo al 26 de mayo de 2014; Museo de Arte de Los Ángeles, del 29 de junio al 28 de septiembre de 2014; El Museo de Bellas Artes, Houston, 2 de noviembre de 2014 - 11 de enero de 2015.
Keywords: Arte coreano -- Exposiciones -- Dinastía Chosŏn, 1392-1910; Corea -- Exposiciones -- Historia; 조선시대문화 -- 조선시대미술 -- 조선불교미술 -- 조선도자 -- 일월오봉도 -- 초상화; Art, Korean -- Chosŏn dynasty, 1392-1910 -- Exhibitions. -- Korea (South) -- Antiquities -- Exhibitions. -- Korea (South) -- Antiquities -- Chosŏn dynasty, 1392-1910 -- Exhibitions. -- Art, Korean -- Choson dynasty